Multiscale characterization of irradiation behaviour of ion-irradiated SiC/SiC composites. (December 2018) - Agarwal, S.; Duscher, G.; Zhao, Y.; Crespillo, M.L.; Katoh, Y.; Weber, W.J.
Abstract: The irradiation tolerance of SiC/SiC composites was studied using 10 MeV Au ion irradiations at 350 °C, for surface doses between 1 and 50 displacements per atom (dpa). Atomic force microscopy and optical profilometry revealed irradiation-induced axial and radial shrinkage of SiC-fibers. At 50 dpa, net fiber shrinkage reached 2.8 ± 0.3%. We conclude that the primary cause of SiC-fiber shrinkage in SiC/SiC composites is the irradiation-induced loss of pre-existing carbon packets, which had occupied 2–3% fiber volume in unirradiated state. A compelling evidence of the carbon packet loss was revealed using a combination of state-of-art conventional transmission electron microscopy (TEM), high resolution TEM, energy-filtered TEM and electron energy loss spectroscopy. The carbon packet volume fraction decreased with increasing dose, reaching near-complete loss after 50 dpa. Carbon packet loss was further confirmed using Raman spectroscopy where the carbon D and G peaks disappeared after irradiation. In contrast, irradiation-induced swelling of 1 ± 0.5% was observed in the matrix after 50 dpa. The study also shows that up to 50 dpa, the multilayer pyrolytic-carbon (PyC) interface in the composite is highly irradiation tolerant as it maintained its morphology, graphitic nature and showed no signs of amorphization. Additionally, Raman spectroscopy revealed a saturation of TEM invisible disorder at 1 dpa for both ultra-fine grains of the fiber and the larger SiC-matrix grains. However, TEM visible extended defect formation such as dislocation loops were only detected in the larger matrix grains, thereby revealing a potential role of grain size on defect accumulation in SiC. Graphical abstract: Image 1